2020
DOI: 10.1161/hypertensionaha.120.15574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Vulnerable Preterm Heart and Circulation on Adult Cardiovascular Disease Risk

Abstract: Preterm birth accounts for over 15 million global births per year. Perinatal interventions introduced since the early 1980s, such as antenatal glucocorticoids, surfactant, and invasive ventilation strategies, have dramatically improved survival of even the smallest, most vulnerable neonates. As a result, a new generation of preterm-born individuals has now reached early adulthood, and they are at increased risk of cardiovascular diseases. To better understand the sequelae of preterm birth, cardiovascular follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 78 publications
2
66
0
5
Order By: Relevance
“…This supports the hypothesis that the higher myocardial mass following preterm birth is driven by cardiomyocyte hypertrophic growth through other mechanisms, such as the adaptation to early hemodynamic changes faced by the immature myocardium ( 3 , 11 ). However, there remains discrepancy between preterm-born adult cohorts, with some demonstrating lower LV mass ( 9 ), which may relate to reduced cardiac endowment with earlier gestations or differences in clinical care across health care systems ( 10 ). We found a strong relationship between ECV and impairments in both CMR- and echocardiography-derived diastolic function measures in the preterm group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the hypothesis that the higher myocardial mass following preterm birth is driven by cardiomyocyte hypertrophic growth through other mechanisms, such as the adaptation to early hemodynamic changes faced by the immature myocardium ( 3 , 11 ). However, there remains discrepancy between preterm-born adult cohorts, with some demonstrating lower LV mass ( 9 ), which may relate to reduced cardiac endowment with earlier gestations or differences in clinical care across health care systems ( 10 ). We found a strong relationship between ECV and impairments in both CMR- and echocardiography-derived diastolic function measures in the preterm group.…”
Section: Discussionmentioning
confidence: 99%
“…In line with an increased cardiovascular risk, left ventricular (LV) morphologic and functional changes in people born preterm are first observed in the neonatal period and continue into infancy, childhood, and young adulthood ( 8 ). These potentially adverse alterations extend across gestational age categories of prematurity and include smaller internal cavity dimensions and volumes, reduced systolic and diastolic function, and an increased rate of hypertrophy from childhood to adulthood ( 8 ), though there is variability in LV mass findings across studies ( 9 , 10 ). This is consistent with findings from animal models of prematurity, which show smaller cardiac dimensions and greater myocardial interstitial fibrosis ( 11 , 12 ).…”
mentioning
confidence: 99%
“…6,7 It is thus conceivable that the observed patterns of cardiac remodeling seen in individuals born preterm make their hearts more vulnerable to chronic insults, such as the hemodynamic stress of sustained blood pressure elevation. Of related concern is that, compared with their term-born peers, individuals born preterm have higher systolic and diastolic blood pressures, 8 with preterm birth now recognized as a risk factor for hypertension in adulthood. 9 While earlier studies have shown associations between cardiac structural and functional alterations with increasing blood pressure, 10,11 they have been limited by small numbers of individuals with blood pressures in the clinically elevated and hypertensive range.…”
mentioning
confidence: 99%
“…These factors may influence not only increased respiratory morbidity in infancy due to cardiac-lung disease [ 33 ] but also cardiac development and increased risk for cardiovascular disease and decreased tolerance to exercise later in life [ 45 ]. Development of cardiac alterations in adulthood, including fibrosis and hypertrophy have been linked to activation of the RAAS, in particular due to angiotensin II [ 1 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%